Evaluation of soil fungi producing dyes for dyeing cloth with mordanting alum and copper sulphate - Suciatmih Suciatmih; Yuliar Yuliar (The East Java Biological Society, 2018)
Isolation of soil fungi was done to find an enviromental friendly dyes for dyeing cloth. The aims of this study include isolation and identification of soil fungi from burning waste, cassava rhizosphere, and compost in Cibinong Science Center Area; and evaluation of dyes potential produced by the soil fungi in combination with alum and copper sulphate mordants. Thirty-six isolates of the soil fungi were successfully isolated from the burning waste, cassava rhizosphere, and compost. These include Aspergillus, Colletotrichum, Emericella, Eurotium, Fusarium, Mucor, Paecilomyces, Penicillium, Rhizopus, and Trichoderma. The soil fungi were dominated by asexual morph (77.78%) of which Aspergillus (3 species and 15 isolates) was found as the most common genus from the three samples. A total of 14 isolates were found potential as dye-producing fungi. These include Aspergil-lus sp. strain R-2 (1 isolate), A. fumigatus (3 isolates), Penicillium sp. strain GRC-1 (5 isolates), Penicillium sp. strain R-3 (1 isolate), Penicillium sp. strain RC-1 (3 isolates), Trichoderma harzianum (1 isolate); and Monascus purpureus (1 isolate; as control). Color intensity produced by fungal dyes in combination with alum and copper sulphate as pre-mordanting agents is higher than alum and copper sulphate as post-mordanting agents.